An Ecostylistics Study of Bode Sowande’s Mammy Water’s Wedding - Adugbe , Rebecca Ibukunoluwa (Unisia, 2024)
Poor waste management practices constitute a serious environmental crisis in both rural and urban centers in Nigeria. Hence ecologically conscious Nigerian literary writers have resorted to the instrumentality of art to interrogate the menace and sensitize the people on the expediency of proper waste management for environmental sustainability. This study analyses how Bode Sowande, in his play Mammy Water’s Wedding, enacts the crisis of water pollution in a typical Nigerian society. Representative excerpts that thematically probe the environmental crisis in the play were purposively selected for qualitative analysis. The study applies Virdis’ (2022) Ecostylistics theoretical framework to analyse the stylistic markers of depicting the decrying the ecosophy of human ecologically hostile behaviour, while advocating the coveted ecosophy of nurturing and protecting the non-human species in the environment. The study reveals that deep-seated poor environmental attitudes exhibited by the defaulting characters are mainly borne out of ignorance and individualistic tendencies which fester the disconnection between humans and the physical world. It also underlines the need for an aggressive advocacy for environmental sustainability to engender harmonious relationships between humans and the environment in Nigerian society.